Can Chinese Mutual Fund Time Market Liquidity? - LI, Xiaoqing (2012)
Extant researches have focused on mutual fund managers’ ability to time market returns or volatility. In this paper, the author offers a new perspective on the traditional timing issue by examining Chinese fund managers’ liquidity timing ability. Using the Chinese mutual fund database, the author finds little evidence that over the period from 2004 to 2012, fund managers cannot demonstrate the ability to time market liquidity in China, i.e., increase (reduce) market exposure in anticipation of more liquidity (illiquidity) markets, at the portfolio level. Different investment categories have diversified levels of liquidity timing potential, among which the aggressive growth, stable growth as well as open-ended funds are more likely to have liquidity timing ability. The author further demonstrates that including return-timing and volatility-timing does not materially affect the insignificance of liquidity timing coefficients. However, some Chinese mutual fund managers do have certain ability in time market liquidity at the individual fund level. What is more, the ability of scale timing liquidity is a new discovery, i.e., mutual fund managers tend to prefer smaller (bigger) market capitalization stocks in anticipation of lower (higher) liquidity market.